Factores de riesgo asociados a ventriculitis en pacientes pediatricos atendidos en el INSN Breña año 2020 – 2021 - Pari Caller, Donny Michael (2024)
Objective: To describe the risk factors associated with ventriculitis in pediatric patients treated at the INSN BREÑA during the period from January to December 2020-2022. Method. A cross-sectional, retrospective and observational study was carried out, the medical records of children between the ages of 1 month and under 15 years of age were reviewed, all hospitalized patients treated at the Pediatric Neurosurgery Service of the Breña National Institute of Child Health during the years 2020-2021. Results. 220 patients were found with the diagnosis of ventriculitis, associated with the different risk factors mentioned, of which 110 are cases of ventriculitis and the other 110 will be controls not associated with ventriculitis with another type of meningitis. Taking as criteria 44% of exposed cases, 28% of unexposed controls, an odds ratio of 2 and a confidence level of 95%. Other data have evaluated behavioral factors in bacterial-dominant ventriculitis, such as the following highly positive skin-compatible cocci, which are present as isolates in 50% to 60% of infections, including coagulase-negative staphylococci, Corynebacterium, Bacillus , Micrococcus or Propionibacterium. And the negative microorganisms, Escherichia coli, Klebsiella, Enterobacter, Pseudomonas aeruginosa and Actinomyces baumannii increased. Conclusión. Ventriculitis is one of the most common ailments in pediatric neurosurgery, and the statistics of this pathology in pediatric patients increase every day, so a study was carried out to learn more about the factors involved, the sociodemographic risk, the severity, and the consequences. neurological. sequelae of this pathology.